The quality of work life scale: validity evidence from Brazil and Portugal - Sinval, J.; Sirgy, J.; Dong-Jin, L.; Marôco, J. (Applied Research in Quality of Life, 2020)
Quality of work life (QWL) is an important construct, based on satisfaction of worker’s needs. It is strongly related to higher work engagement and lower burnout. To properly establish comparisons between countries’ QWL with a psychometric instrument, the measure must show validity evidence, namely in terms of measurement invariance. This study aims to assess the validity evidence of the Quality of Work Life Scale (QWLS) by examining the internal structure of the measure (i.e., dimensionality, reliability, and measurement invariance) and its relations with other variables such as burnout and work engagement. The measure was tested using a total sample of 1163 workers, 566 workers from Portugal, and 597 from Brazil. The data had a good fit to the QWLS second-order model and good reliability estimates for the two countries. Full-uniqueness measurement invariance was achieved for data for Portugal and Brazil and for gender too. The measure also demonstrated good nomological validity evidence by successfully predicting burnout and work engagement.